2012
DOI: 10.1021/ie302106w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Properties of the Incorporation of a Novel Reactive Phosphorus- and Sulfur-Containing Flame-Retardant Monomer into Unsaturated Polyester Resin

Abstract: A novel reactive phosphorus-and sulfur-containing flame-retardant monomer [di(allyloxybisphenol sulfone) phenoxy phosphonate, DASPP] was successfully synthesized and well characterized. Various amounts of DASPP were incorporated into the unsaturated polyester by radical bulk polymerization. The thermal properties and flammability of the flameretardant unsaturated polyester resin (FR-UPR) samples were investigated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), limiting oxygen inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Dai et al [21] reported the efficiency of a sulfoxide and phosphate containing compound on polyester thermoset. Expecting the same effect in an epoxy thermoset, a thiol bearing a phosphonate group was used to partially or totally functionalize the epoxy functions of the P3EP.…”
Section: Synthesis Of Diethyl(3-mercaptopropyl)phosphonate (Sp)mentioning
confidence: 99%
“…Dai et al [21] reported the efficiency of a sulfoxide and phosphate containing compound on polyester thermoset. Expecting the same effect in an epoxy thermoset, a thiol bearing a phosphonate group was used to partially or totally functionalize the epoxy functions of the P3EP.…”
Section: Synthesis Of Diethyl(3-mercaptopropyl)phosphonate (Sp)mentioning
confidence: 99%
“…Mineral fillers such as aluminum trihydrate (ATH) are also effective FRs, but only at high loadings. This leads to high viscosities of the UP resin causing problems in processing and the deterioration of material properties …”
Section: Introductionmentioning
confidence: 99%
“…Recently, phosphorus-containing compounds, as halogen-free flame retardants, have received considerable attention [6][7][8]. Generally, there are two methods used to prepare phosphorus UPR composites.…”
Section: Introductionmentioning
confidence: 99%